500 (N[EDEWEROW EWROPEJSKOJ VIWOPISI(B.s - (No(B.(Nw(B.(NmOROZOWAs ((NmOSKWAs (NaBRISs, 2019)
(Nw AL_BOME PREDSTAWLENO (B500 (NWYDA@]IHSQ(B, (NZNAKOWYH DLQ WSEJ MIROWOJ KULTURY PROIZWEDENIJ EWROPEJSKOGO IZOBRAZITEL_NOGO ISKUSTWA h(BIII-(NPERWOJ POLOWINY hh WEKA(B,(NOT TWORENIJ WELIKOGO REFORMATORA VIWOPISI dVOTTO DI bONDONE(B, (NOTKRYW[EGO PERIOT EWROPEJSKOGO PERIOD EWROPEJSKOGO wOZROVDENIQ(B,(NDO RABOT GENIAL_NOGO MASTERA S@RREALIZMA sAL_WADORA dALI(B.s